2019
DOI: 10.1086/702643
|View full text |Cite
|
Sign up to set email alerts
|

Pinnule and Stomatal Size and Stomatal Density of Living and Fossil Bowenia and Eobowenia Specimens Give Insight into Physiology during Cretaceous and Eocene Paleoclimates

Abstract: Editor: Michael T. DunnPremise of research. This study compares the pinnule morphology of three fossil Bowenia species, one Eobowenia (fossil) species, and several Bowenia fossil pinnule fragments with the two extant Bowenia species.Methodology. Pinnule area, stomatal density, and size have been measured on fossil and extant specimens.Measures have been correlated with solar radiation and temperature to ascertain any correlations. Environment and climate variables have been chosen, as they have changed since t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The tree also confirms the relationship between the Mesozoic genus Paracycas Harris and extant Cycas. The genus Eobowenia is confirmed as sister to extant Bowenia, strengthening inferences on its understory habit based on comparison with other fossil and extant species of this lineage (Hill et al, 2019b).…”
Section: Phylogeny Of Cycadssupporting
confidence: 51%
See 1 more Smart Citation
“…The tree also confirms the relationship between the Mesozoic genus Paracycas Harris and extant Cycas. The genus Eobowenia is confirmed as sister to extant Bowenia, strengthening inferences on its understory habit based on comparison with other fossil and extant species of this lineage (Hill et al, 2019b).…”
Section: Phylogeny Of Cycadssupporting
confidence: 51%
“…Our results validate some previous suggestions of relatedness between fossil taxa and extant genera (Hill, 1978 ; Carpenter, 1991 ; Kvaček, 2002 ; Su et al ., 2014 ; Erdei et al ., 2018 ; Hill et al ., 2019a ). Previously puzzling forms, such as Eostangeria (Barthel, 1976 ; Kvaček & Manchester, 1999 ; Uzunova et al ., 2001 ), appear to represent transitional forms between the Zamia ‐ Microcycas clade and the extremely derived genus Stangeria , combining the epidermal anatomy of the former with the unique macromorphology of the latter (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Many fossil taxa that were originally identified as close relatives of extant genera have been identified as potential members of entirely extinct lineages, with little shared evolutionary history with the modern species (Erdei et al 2019;Barone Lumaga et al 2015). The few fossil cycads for which a relationship between fossil and extant taxa has been validated by phylogenetic analyses (Coiro & Pott 2017) show no evidence of a drastic response of SD or stomatal size to pCO 2 (Hill et al 2019). The different response of cycads and Bennettitales to pCO 2 is thus not surprising in the light of morphological phylogenetic analyses showing that the two groups are only distantly related (Crane 1985;Doyle & Donoghue 1986;Doyle, 2008;Hilton & Bateman, 2006;Coiro et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that we can quantify the response of leaves of extant plant species to climatic conditions and use this knowledge to infer how closely related species responded to climate change in the past, based on the anatomy of fossil leaves. Leaf measures that have been analysed in the past include leaf area and shape as a response to the mean annual temperature [1]; carbon isotope fractionation as a response to the mean annual precipitation [2]; stomatal size and density as responses to light availability and the temperature [3]; leaf size as an indicator of the growth temperature (although this has been criticised for over-use [4]); many novel physiognomic characters such as the tooth area and number of teeth on leaf margins as responses to the mean annual temperature [5]; and a combination of leaf characters to reconstruct how open the vegetation was [4].…”
Section: Introductionmentioning
confidence: 99%